A SERS and fluorescence dual-channel microfluidic droplet platform for exploring telomerase activity at the single-cell level. Issue 22 (6th October 2022) - Qi, Guohua; Du, Xing; Yi, Xuan; Wang, Minmin; Zhu, Hongyan; Sun, Dan
Abstract : Overview of the workflow of the fluorescence and SERS dual-channel microfluidic droplet system for encapsulating a single cell and detecting telomerase. Abstract : Telomerase is a significant biomarker for potential early cancer diagnosis and therapy. Exploring telomerase activity in single cells presents great challenges due to the complexity and small amount of total proteins in telomerase as well as the lack of an effective amplification method for its analysis. Herein, we developed a surface-enhanced Raman spectroscopy (SERS) and fluorescence dual-channel microfluidic droplet platform for the in situ and highly sensitive determination of low-abundance telomerase activity in single cells. In this work, the nanoprobe is composed of gold nanoparticles (AuNPs) functionalized by a telomerase primer and signal sequence (a Cy5-labeled DNA strand). The dual-signal switching of the SERS turn-off and fluorescence turn-on mechanisms for the Cy5 response to telomerase allows for the highly sensitive and reliable determination of telomerase at the single-cell level. As a result, the SERS–fluorescence microdroplet platform exhibits an excellent performance for the efficient investigation of cell heterogeneity upon telomerase expression and the dynamic monitoring of variations in intracellular telomerase activity during treatment with a telomerase inhibitor. The proposed platform will help to decipher the heterogeneity of cell populations and is potentially applicable in the clinical diagnosis of diseases related to telomerase activity.